Proteome analysis of Bordetella pertussis isolated from human macrophages - Lamberti, Yanina; Cafiero, Juan Hilario; Surmann, Kristin; Valdez, Hugo; Holubova, Jana; Večerek, Branislav; Sebo, Peter; Schmidt, Frank; Völker, Uwe; Rodriguez, Maria Eugenia (Journal of proteomics, 2016)
UNLABELLED: Previous studies have shown that B. pertussis survives inside human macrophages in non-acidic compartments with characteristics of early endosomes. In order to gain new insight into the biology of B. pertussis survival in host cells, we have analyzed the adaptation of the bacterial proteome during intracellular infection. The proteome of B. pertussis 3 h and 48 h after infection of human macrophage-like THP-1 cells was examined by nano-liquid chromatography combined with tandem MS and compared to the protein profile of extracellular B. pertussis growing in the same cell culture medium. Compared with extracellular bacteria, almost 300 proteins out of 762 identified proteins displayed altered levels in intracellular B. pertussis. Functional analyses of the proteins displaying altered abundance revealed enrichment of proteins involved in stress response, iron uptake, cellular metabolism, transcriptional regulation, and virulence. To our knowledge, this is the first analysis of the B. pertussis proteome during adaptation to the intramacrophage environment and the data provide new clues for understanding B. pertussis adaptation and pathogenesis. BIOLOGICAL SIGNIFICANCE: B. pertussis is a respiratory pathogen that has adapted exclusively to the human host. Despite high vaccination rates, whooping cough remains a serious threat to human health and its incidence has been increasing in recent years in vaccinated populations. The mechanisms that allow this pathogen to evade immune clearance, persist in the host, and cause a prolonged paroxysmal cough are still poorly understood. Recent studies regarding B. pertussis survival inside host cells and the cellular response to this bacterial infection indicate that B. pertussis may have an intracellular phase during infection which probably contributes to persistence and vaccine failure. In this study we provide the first global proteome profile of B. pertussis within macrophages. The data provide novel insights into the adaptive responses elicited by these bacteria for physiological adaptation to the host environment.
Keywords: nádorové buněčné linie; Bacterial Proteins; proteom; THP-1 cells; makrofágy; Proteome; Macrophages; Cell Line, Tumor; Humans; Intracellular survival; lidé; Bordetella pertussis; Host–pathogen interaction; Proteomics; bakteriální proteiny